2010
DOI: 10.1590/s0482-50042010000300011
|View full text |Cite
|
Sign up to set email alerts
|

A síndrome anserina

Abstract: Dor no joelho é uma condição comum na clínica diária e a patologia anserina, também conhecida como pata de ganso, tem sido considerada uma das principais causas. O diagnóstico tem sido realizado de maneira eminentemente clínica, o que tem gerado equívocos. Os pacientes queixam-se tipicamente de dor na parte medial do joelho, com sensibilidade na porção ínferomedial. Estudos de imagem têm sido realizados para esclarecer se tais pacientes possuem bursite, tendinite ou ambos os distúrbios na região conhecida como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
(36 reference statements)
3
31
1
1
Order By: Relevance
“…Numerous studies have demonstrated the role obesity plays in the development of osteoarthritis [13], cartilage defects [47], bone marrow lesions [68], pes anserine syndromes [9], and patello-femoral osteoarthritis [10]. These changes are largely attributed to a combination of increased load and altered joint biomechanics [11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the role obesity plays in the development of osteoarthritis [13], cartilage defects [47], bone marrow lesions [68], pes anserine syndromes [9], and patello-femoral osteoarthritis [10]. These changes are largely attributed to a combination of increased load and altered joint biomechanics [11].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of pes anserinus syndrome is higher in women who are overweight and 50-80 years old, especially if they also have osteoarthritis of the knees, valgus deformities or pes planus [7, 10, 12]. A second etiology includes osteochondroma, as well as trauma, retraction of posterior thigh muscles, damage to the medial meniscus, infection, and foreign body reaction [10, 14].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pes anserinus syndrome is higher in women who are overweight and 50-80 years old, especially if they also have osteoarthritis of the knees, valgus deformities or pes planus [7, 10, 12]. A second etiology includes osteochondroma, as well as trauma, retraction of posterior thigh muscles, damage to the medial meniscus, infection, and foreign body reaction [10, 14]. The differential diagnosis of pes anserinus syndrome considers lesions with pain infero-medial to the knee joint, such as the medial meniscus; osteoarthritis of the medial compartment of the knee; lumbar radiculopathy; lesions in the medial collateral ligament; and insufficiency fractures [10, 15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations